The changing relative price of skill-intensive goods - Christian Gäckle; Ingmar Schustereder; Patricia Waeger (Kiel Institute for the World Economy (IfW), 2006)
Based on the conceptual results of Findlay, Grubert (1959) and Krugman (2000) we analyze the movement of the relative price of skill-intensive goods under skill-biased technological change and the countervailing effect of increasing world-wide supply of low-skilled-labor. While the labor supply effect has become more important in the last two decades, we show that the distinction between large and small technological progress is crucially important for analyzing the changing pattern of relative price developments.
Keywords: F11; F14; F16; 330; skill-biased technological change; unskilled-labor supply; relative goods prices